2020
DOI: 10.1159/000505830
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission of Relapsed Hodgkin’s Lymphoma following Brentuximab Vedotin and Gemcitabine Combination Therapy with Severe Hypotension as Possible Treatment-Related Adverse Event: A Case Report

Abstract: A 40-year-old Asian female with heavily treated relapsed Hodgkin's lymphoma showed complete remission (CR) after receiving 8 cycles of brentuximab vedotin (BV) in combination with gemcitabine as 4th line treatment. The patient remained in CR at the 18-month post-treatment follow-up. She developed severe hypotension (50/36 mm Hg) with upper and lower limb petechiae and edema after the addition of gemcitabine on the 6th cycle of BV. This adverse event resolved after 3 days of treatment with vasopressor and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…These data may be valuable because to our knowledge, there have been no previous reports showing the pathological findings or evaluation of foci that have achieved remission status with chemotherapy for HL. There have been reports of cases of recurrent HL controlled with intense chemotherapy, confirmed by FDG‐PET/CT 7 . The usefulness of biomarkers, such as thymus and activation‐regulated chemokine as prognostic and treatment monitoring for HL has also been reported 8,9 .…”
Section: Discussionmentioning
confidence: 96%
“…These data may be valuable because to our knowledge, there have been no previous reports showing the pathological findings or evaluation of foci that have achieved remission status with chemotherapy for HL. There have been reports of cases of recurrent HL controlled with intense chemotherapy, confirmed by FDG‐PET/CT 7 . The usefulness of biomarkers, such as thymus and activation‐regulated chemokine as prognostic and treatment monitoring for HL has also been reported 8,9 .…”
Section: Discussionmentioning
confidence: 96%
“…For instance, the combination of gemcitabine with Brentuximab vedotin has been shown to produce positive outcomes in other hematological malignancies. 20 1.8 mg/kg. Within the first four cycles of therapy 24 (57%) patients had a complete response with a tolerable toxicity profile.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the combination of gemcitabine with Brentuximab vedotin has been shown to produce positive outcomes in other hematological malignancies 20 . Cole et al demonstrated the safety and efficacy of gemcitabine in association with brentuximab vedotin in 42 patients with refractory Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…10 Symptom presentation occurred 2 to 3 days after intravenous gemcitabine administration. 3,4 Two other cases took 6 to 10 days to manifest, so the patients underwent exhaustive workups to arrive at gemcitabine-induced SCLS as a diagnosis of exclusion. 5,7 In all the cases, the symptoms resolved after treatment with intravascular volume repletion, corticosteroids, diuretics, and occasionally vasopressors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Gemcitabine's intravenous use has been associated with several side effects including systemic capillary leak syndrome (SCLS), a rare disorder with a high mortality rate thought to arise from endothelial damage and characterized by rapid-onset edema, hypotension, hemoconcentration, and hypoproteinemia. Although scattered case reports of gemcitabine-induced SCLS have been described, [2][3][4] there are no reports of SCLS after intravesical gemcitabine administration. We describe a case of postoperative vasoplegia associated with intravesical gemcitabine suspected to be SCLS.…”
Section: Persistent Postoperative Vasoplegia After Ureteronephrectomy...mentioning
confidence: 99%